Bipedality from locomotor autonomy to adulthood in captive olive baboon (Papio anubis): Cross‐sectional follow‐up and first insight into the impact of body mass distribution. Issue 1 (21st August 2015) - Druelle, François; Aerts, Peter; Berillon, Gilles
ABSTRACT: Objective: Despite that the biomechanics of standing and walking bipedally has been extensively studied in nonhuman primates, the morphological features that may constrain, or facilitate, the control of balance and thus of the spontaneous occurrence of bipedal behavior are poorly known. We aim to test the relationship between body mass distribution and bipedal behavior using a nonhuman primate species, the olive baboon, Papio anubis, raised in captivity. Materials and Methods: We collected quantitative data on the frequency and duration of bipedalism together with morphometrics on a sample of 22 individuals. We used ontogenetic changes as a natural experiment that provides insights into the impact of morphology. Specifically we focus on 1) quantifying how body mass distribution changes from infancy to adulthood in baboons; and 2) whether the different patterns of mass distribution influence the behavioral variables, i.e., a) the frequency and b) the duration of bouts of bipedal behavior realized in different activity contexts. Results: With regard to assisted bipedal behaviors, the duration and frequency of bouts of standing, contrary to walking, are significantly related to age. With regard to unassisted bipedal behaviors, no correlation to age is observed; the bout duration of walking is strongly correlated to body mass and mass distribution, contrary to the frequency of walking as well as the bout duration and frequency of bipedal standing. Discussion: Our results suggest a close relationship between the pattern of mass distribution and the mechanism of balance control in the spontaneous bipedal walking of baboons. The mechanical effects of the pattern of mass distribution on the ability to perform bipedally in extant nonhuman primates are discussed in the context of the evolution toward habitual bipedalism. Am J Phys Anthropol 159:73–84, 2016. © 2015 Wiley Periodicals, Inc.